Achieving an Active Lifestyle within a Walkable Environment: Assessment of Before and During the COVID-19 Pandemic (International Journal of Built Environment and Sustainability, 2022)
Having an active lifestyle has been regarded as one of the main factors for maintaining a healthy and happy life. However, previous studies have pointed out that most Malaysian adults are reported to be physically inactive due to lifestyle changes such as increasingly sedentary lifestyles, decreased physical activity (PA), and growing reliance on automobiles for mobility. Subsequently, the COVID-19 pandemic has further impacted the quality of the urban population’s active lifestyles, particularly the disruption resulting from movement restriction control orders which has limited the ability to maintain an active lifestyle. This scenario has the potential to negatively impact the health and mental state of the population if it continues without intervention by relevant stakeholders. Therefore, this study examined the patterns of PA and body mass index (BMI) and assessed the association between PA and a walkable environment to maintain an active lifestyle in Kuala Lumpur city centre before and during the COVID-19 pandemic. In this study ‘walkable environment’ refers to a physical attribute that encourages walking for functional and recreational purposes and ‘active lifestyle’ refers to walking being the main physical PA that contributes to health as part of people’s regular routine. This study adopted the mixed method approach through an online questionnaire survey, combined with the observation of selected areas and content analysis of written documents. The findings show that most respondents perceived that walking was the main PA that contributes to health. In terms of effects, walkable environments have been shown to have a positive impact on PA and health by encouraging an active lifestyle.
Keywords: Physical Activity (PA), Active Lifestyle, Body Mass Index (BMI), Walking, Walkable Environment